Effects of carnitine palmitoyltransferases on cancer cellular senescence. Issue 2 (2nd August 2018) - Guan, Lihuan; Chen, Yixin; Wang, Yongtao; Zhang, Huizhen; Fan, Shicheng; Gao, Yue; Jiao, Tingying; Fu, Kaili; Sun, Jiahong; Yu, Aiming; Huang, Min; Bi, Huichang
Abstract : The carnitine palmitoyltransferase (CPT) family is essential for fatty acid oxidation. Recently, we found that CPT1C, one of the CPT1 isoforms, plays a vital role in cancer cellular senescence. However, it is unclear whether other isoforms (CPT1A, CPT1B, and CPT2) have the same effect on cellular senescence. This study illustrates the different effects of CPT knockdown on PANC‐1 cell proliferation and senescence and MDA‐MB‐231 cell proliferation and senescence, as demonstrated by cell cycle kinetics, Bromodeoxyuridine incorporation, senescence‐associated β‐galactosidase activity, colony formation, and messenger RNA (mRNA) expression of key senescence‐associated secretory phenotype factors. CPT1C exhibits the most substantial effect on cell senescence. Lipidomics analysis was performed to further reveal that the knockdown of CPTs changed the contents of lipids involved in mitochondrial function, and lipid accumulation was induced. Moreover, the different effects of the isoform deficiencies on mitochondrial function were measured and compared by the level of radical oxygen species, mitochondrial transmembrane potential, and the respiratory capacity, and the expression of the genes involved in mitochondrial function were determined at the mRNA level. In summary, CPT1C exerts the most significant effect on mitochondrial dysfunction‐associated tumor cellular senescence among the members of the CPT family, which further supports the crucial role of CPT1C in cellular senescence and suggests that inhibition of CPT1C may represent as a new strategy for cancer treatment through the induction of tumor senescence. Abstract : This study revealed that carnitine palmitoyltransferase 1C (CPT1C) knockdown exhibited the strongest impact on cell growth arrest and senescence, lipid change and accumulation, and mitochondrial dysfunction among all members of the CPT family. In addition, only knocking down CPT1C could downregulate the protein expression of c‐Myc and cyclin D1 and upregulate the cell cycle inhibitor p27 significantly, which contributes to the potential molecular mechanism of CPT1C knockdown‐induced cellular senescence.